WORK LIFE BALANCE: IMPLEMENTASI TOOL KIT WORK LIFE BALANCE PADA BEBAN KERJA - Hurriyati, Dwi; Aris, Aris Giovany (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
Nowadays, The imbalance between work and life balance is one of the main issues that many people confront in the workplace these days. This is demonstrated by high overtime, tight deadlines, and the propensity to take work home. Through the use of time management and relaxation techniques, this project seeks to develop and deploy a toolbox in the form of an e-module that will enhance work-life balance. Descriptive qualitative methods, semi-structured interviews, and observations were used to gather data. The information was then subjected to a thematic analysis. The findings demonstrated that the e-module, which incorporates mindfulness exercises, reflective journaling, and the Pomodoro method, can assist individuals in bettering their work-life balance, managing their time, and lowering stress. creating long-term plans for managing human resources.